Evidence-Based Policy Making in the Social Sciences : Methods That Matter - Evans, Mark, 1965 February 17-; Stoker, Gerry (Book collections on Project MUSE., 2017)
The purpose of this edited work is to make the case for why the social sciences are more relevant than ever before in helping governments solve the wicked problems of public policy. It does this through a critical showcase of new forms of discovery for policy-making drawing on the insights of some of the world's leading authorities in public policy analysis.